Análisis automatizado de neuronas de la médula espinal mediante la utilización de tres programas de análisis de imágenes - Portiansky, Enrique Leo::http://voc.sedici.unlp.edu (Analecta Veterinary, 2015)
Automated detection of free elements (microorganisms, cells, minerals, etc.) does not have the same complexity as that necessary to recognize and subsequently morphometrically analyse elements involved in a context such as particular cells within a tissue. In this technical report, alternatives for the identification of neurons in the gray matter of a rat spinal cord segment using three different digital image analysis software packages are described. The results are compared and the advantages and differences of the performed procedures are discussed.